Women's land tenure security and climate action: evidence, barriers to evidence, and the need for collaboration - Gumucio, Tatiana; Jacobs, Krista; Sanjak, Jolyne; McMonagle, Rachel; Roberts, Beth (Gender and development, 2025)
The complex connections between women's land tenure security (WLTS) and climate action need to be understood to inform investments and plans for mitigating climate change and achieving more resilient futures. We synthesise empirical evidence using a conceptual framework with three pathways through which improving WLTS could contribute to climate change mitigation, adaptation, and resilience: long-term land investments, increased range of response options, and sustainable management of forest resources. Although emerging evidence supports WLTS as a route to climate change mitigation and adaptation, data gaps and an insufficiently clear framing of mitigation and adaptation outcomes impede analysis of the impacts of WLTS on mitigation and adaptation. Applying conceptual frameworks for resilience can clarify, organise, and help communicate the expected adaptation and resilience outcomes. Data on women's bundle of land and resource rights within collective systems, their completeness and durability, and equity compared with men's rights in the same system are needed to analyse and make more visible WLTS and its potential influence on mitigation and adaptation actions. Researchers, governments, and funders can collaborate to generate the data and evidence needed and assess already existing relevant data. Initiatives to facilitate closer collaboration across land and climate change sectors can help motivate the cross-sector collaboration needed to address data gaps.